Global political ethnography: A methodological approach to studying global policy regimes - Finn Stepputat; Jessica Larsen (Danish Institute for International Studies (DIIS), 2015)
At a time when changing world orders, new actors, and new technologies transform global policy regimes, this DIIS Working Paper argues that a methodology for studying such regimes ethnographically seem to be emerging across various disciplines. The purpose of the paper is twofold: firstly, we seek to contribute to the dialogue on ethnographic and practice-oriented approaches that is growing across disciplines, from anthropology to political science and International Relations, and provide some common ground for this dialogue. Secondly, by reviewing an extensive literature, we focus on methodological discussions concerning how to approach the highly complex global policy processes that are currently developing. What are the appropriate empirical scale(s) and units of analysis of a global political ethnography? How do we identify sites, encounters, situations and materials where ethnographic approaches can generate different and maybe more critical insights than more conventional approaches? And how are the voices and practices of actors operating at different scales and in different sites balanced and connected in the policy analysis?
Keywords: 300; Defense and security policy; Global economic governance; High-risk migration; Peacebuilding and democratization; Migration and development; Migration and border management; Climate change and environment; Development policies and practice